Peanuts : It's a Mystery, Charlie Brown - Schulz, Charles M. (New York : Random House, 1975)
Sally is at her wit's end due to a science project. She steals a bird's nest hoping to end her problems but only succeeds in creating more.
"A Charlie Brown special."
Keywords: Mystery and detective stories; Schools -- Fiction; Cartoons and comics; Picture Book